Method for determining the strength of general immunity (information letter) - Popov, Mycola; Minukhin , Valerii; Martynenko , Olexsandr; Liadova , Tetiana; Volobuieva , Olha; Popova , Alisa; Ohnivenko , Olena (Annals of Mechnikov's Institute, 2025)
Determination of the strength of general immunity is carried out by quantitative and qualitative characteristics of effector molecules and immune cells, which appear as a result of the development of both humoral and cellular immune reactions. Their level and activity reflect all stages of the immune process. It is proposed to determine the level of antibody production in response to ADP vaccination, or the level of antibodies in previously vaccinated, the potential of lymphocytes to produce INF, the biocidality of blood neutrophils, the infectious index.